The Impact of an Authentic Sports Leadership Program for Coach - Soto Garcia, Diego; García Herrero, Juan Antonio; Carcedo, Rodrigo Jesús; Sánchez García, Mario (Frontiers in Psychology, 2021)
Abstract Purpose: This paper studies the effects of authentic sports leadership training on coaches' self-perception of their own authentic leadership, perceived justice, competence, overall self-efficacy, and collective efficacy. Additionally, players' perceptions of their coaches with respect to their authentic leadership, perceived justice, competence, collective efficacy, satisfaction with the coach, and support for basic psychological needs were analyzed. Design: 25 football and handball coaches were randomly assigned to two groups. 15 coaches made up the experimental group that carried out the training leadership program, while 10 coaches made up the control group, carrying out no training whatsoever. A total of 248 football and handball players participated in this study; 136 were led by coaches who participated in the training program, and 112 by coaches who did not participate in the program. Results: The results of this study indicate that coaches' self-perception is positively influenced after having received training in the variables of authentic leadership, perceived justice, competence, overall self-efficacy, and collective efficacy. Players whose coaches were part of the program perceive them as being more competent as coaches. Conclusions: The effects of an authentic sports leadership training program are effective for coaches and players alike.